Particularities of Accounting and of Valuating the Financial Reporting Informational Content for a Fitness Center - Bogdan Cosmin GOMOI (CECCAR Business Review, 2024)

(untitled)
In today’s context, with the interference of technology in the workplace, peoples activities are increasingly sedentary. So, naturally, fitness is becoming more and more popular, fitness centres mushrooming and the variety of products and services on offer is on the rise. They carry out a mixed activity, both service provision (through the packages offered) and commercial (through the sale of supplements and equipment), with a specific accounting approach that naturally outlines certain patterns at the level of the financial statements. This article aims to capture the particularities of current accounting and the valorisation of the information from financial reports at the level of a fitness center in Arad, which appeared on the market in the post-pandemic context. The accounting specificity will be emphasised by means of current operations, and the financial reporting specificity will be highlighted by determining and interpreting a number of relevant static and dynamic indicators.